The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1146/annurev.soc.24.1.291
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Drugs, and Violence

Abstract: A review of the scientific literature on the relationship between alcohol and violence and that between drugs and violence is presented. A review and analysis of three major theoretical approaches to understanding these relationships are also presented. A number of conclusions are reached on the basis of these efforts. First, despite a number of published statements to the contrary, we find no significant evidence suggesting that drug use is associated with violence. Second, there is substantial evidence to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
183
1
12

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(205 citation statements)
references
References 64 publications
9
183
1
12
Order By: Relevance
“…First, drug users do commit a high percentage of crime, and the frequency of their criminal activity, particularly property offenses, tends to be directly related to their level of drug use. [5][6][7][8][9][10][11] Second, drug treatment provided to offenders has at least moderate effects in reducing drug use and criminal activity and in improving other areas of social functioning. [12][13][14][15][16] Finally, coerced clients and those who may not recognize or acknowledge that they have a drug problem can, through treatment participation and interaction with other clients, become engaged in treatment and do as well as voluntary clients.…”
Section: Introductionmentioning
confidence: 99%
“…First, drug users do commit a high percentage of crime, and the frequency of their criminal activity, particularly property offenses, tends to be directly related to their level of drug use. [5][6][7][8][9][10][11] Second, drug treatment provided to offenders has at least moderate effects in reducing drug use and criminal activity and in improving other areas of social functioning. [12][13][14][15][16] Finally, coerced clients and those who may not recognize or acknowledge that they have a drug problem can, through treatment participation and interaction with other clients, become engaged in treatment and do as well as voluntary clients.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that acute intoxication by alcohol (below sedating levels) is related to aggression when an individual is provoked (Bushman, 1997;Lipsey et al 1997). This increased aggression under conditions of alcohol intoxication in the laboratory is best explained by the fact that alcohol causes changes within a person that increase the risk for aggression, such as reduced intellectual functioning, reduced self-awareness, selective disinhibition, and the inaccurate assessment of risks (Chermack and Giancola 1997;Ito, Miller, and Pollock 1996;Parker and Auerhahn 1998). These same alcohol-induced changes may put a person at risk for nonaggressive crimes, although less research and theorizing have been applied to psychopharmacological explanations for property crime (Goldstein 1985;White and Gorman 2000).…”
mentioning
confidence: 99%
“…Psychopharmacological effects of alcohol that have been postulated to increase the risks for delinquency include impairment in communication, which involves provoking others and being easily angered; increased risk taking; an unawareness of the consequences of one's own behavior; and expectancies that alcohol use causes aggression (Bushman 1997;Chermack and Giancola 1996;Ito et al 1996;Parker and Auerhahn 1998;White 1997aWhite , 1997b). An alternative explanation may be that the use of drugs is a social activity, and thus, while using drugs, adolescents may be in the company of peers who encourage or reinforce illegal behavior (Fagan 1993;White 1990).…”
mentioning
confidence: 99%
“…A number of researchers have examined the correlation between alcohol abuse and intimate partner violence, as well as the relationship between alcohol-induced aggression and violent behavior in general (Parker and Auerhahn 1998). Research has clearly shown a statistically significant relationship between alcohol abuse and violence between partners (Miller et al 1989;O'Farrell et al 1999;Testa et al 2003;Thompson and Kingree 2006).…”
Section: Alcohol Abuse and Intimate Partner Violencementioning
confidence: 99%